2009
DOI: 10.1007/978-90-481-2949-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of DU Particles from Kosovo and Kuwait

Abstract: Large amounts of DU material has been released to the environment in Kosovo and Kuwait due to the use of depleted uranium (DU) ammunition during the 1991 Gulf war and the 1999 Balkan conflict. Following the impact of metallic DU penetrators on solid targets, DU particles are dispersed and ignited, and uranium in the particles is oxidized. Following inhalation or ingestion of DU particles, the amount of DU that is absorbed into the blood and distributed to tissues and organs will largely depend on the particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…(nuclear fuel partially burned) caused the dispersion of particles containing Pu and U (Lind et al, 2004;Jiménez-Ramos et al, 2006) over a terrestrial area of about 2.3 km 2 (Iranzo et al, 1987) situated close to the Mediterranean. A similar accident occurred at Thule, Greenland, 1968, where a B-52 bomber carrying four thermonuclear bombs caught fire and crashed on the ice at Bylot Sound.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…(nuclear fuel partially burned) caused the dispersion of particles containing Pu and U (Lind et al, 2004;Jiménez-Ramos et al, 2006) over a terrestrial area of about 2.3 km 2 (Iranzo et al, 1987) situated close to the Mediterranean. A similar accident occurred at Thule, Greenland, 1968, where a B-52 bomber carrying four thermonuclear bombs caught fire and crashed on the ice at Bylot Sound.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…These methods are also applied in the area of nuclear forensics to detect and prevent the illicit trafficking of nuclear material, , as well as for monitoring and risk assessment of radioactively polluted sites. In the latter case, particle analysis has been introduced and used during the past decade as it has been shown that most of the activity released is carried by particles. These studies underline the importance of characterizing particulate effluents as the impacts on health and the environment ultimately depend on the chemical and physical composition of the particles.…”
mentioning
confidence: 99%
“…In general, radionuclide composition, activity concentration, isotope ratios, and burn-up will reflect the emitting source of released particles, while particle characteristics such as size distribution, crystallographic structure, and oxidation state ultimately depend on their release scenarios (i.e., affected by temperature and pressure, presence of air) and histories . Volatility of the released material as well as particle characteristics are determinant in “hot” particle ecosystem behavior …”
Section: Environmental Actinide Particlesmentioning
confidence: 99%
“…Actinide containing particles from military use span a size range from submicrometer to several hundred micrometers . Pure An or AnO x particles (An = Pu,U) and mixtures thereof have been reported.…”
Section: Environmental Actinide Particlesmentioning
confidence: 99%
See 1 more Smart Citation